2016
DOI: 10.1681/asn.2015080916
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Substrate and Risk of Mortality in Incident Hemodialysis

Abstract: The single leading cause of mortality on hemodialysis is sudden cardiac death. Whether measures of electrophysiologic substrate independently associate with mortality is unknown. We examined measures of electrophysiologic substrate in a prospective cohort of 571 patients on incident hemodialysis enrolled in the Predictors of Arrhythmic and Cardiovascular Risk in End Stage Renal Disease Study. A total of 358 participants completed both baseline 5-minute and 12-lead electrocardiogram recordings on a nondialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 46 publications
3
34
2
Order By: Relevance
“…Unlike the SVG, QRS-T angle (also reflected in a parameter known as the total cosine of the R-to-T), has been evaluated in numerous risk stratification studies. Increased QRS-T angle has been associated with total mortality and arrhythmic events in patients after myocardial infarction [34], total mortality, cardiovascular mortality, and sudden cardiac death in patients with end-stage renal disease on dialysis [35,36], more frequent appropriate implantable cardioverter-defibrillator therapies [37], and sudden cardiac death in the general population [29,38,39]. …”
Section: Other Ecg Parameters Based On the Svgmentioning
confidence: 99%
“…Unlike the SVG, QRS-T angle (also reflected in a parameter known as the total cosine of the R-to-T), has been evaluated in numerous risk stratification studies. Increased QRS-T angle has been associated with total mortality and arrhythmic events in patients after myocardial infarction [34], total mortality, cardiovascular mortality, and sudden cardiac death in patients with end-stage renal disease on dialysis [35,36], more frequent appropriate implantable cardioverter-defibrillator therapies [37], and sudden cardiac death in the general population [29,38,39]. …”
Section: Other Ecg Parameters Based On the Svgmentioning
confidence: 99%
“…Recently, the spatial QRS-T angle was assessed in a prospsective cohort of 358 hemodialysis patients (mean age 55 years, 59% male, 37% with CAD, 75% with LVH, and mean LVEF 66%), and after multivariable adjustment, spatial QRS-T angle ≥75° was associated with all-cause mortality (HR 2.38, p=0.001), cardiovascular mortality (HR 2.99, p=0.01), and SCD (HR 4.52, p=0.03) [22]. The optimal abnormal cut-off value of spatial QRS-T angle for use in the ESRD population will require further study, but this ECG parameter, which integrates abnormalities of both depolarization and repolarization, shows promise as a non-invasive SCD risk stratification tool.…”
Section: Spatial Qrs-t Anglementioning
confidence: 99%
“…Between 8–25% of hemodialysis patients will have an abnormal SAECG [22,26,27], and various small studies have found that a hemodialysis session can worsen or improve the SAECG [27,28]. Increases in filtered QRS duration after hemodialysis have been associated with decreases in serum potassium [27].…”
Section: Signal Averaged Ecgmentioning
confidence: 99%
See 1 more Smart Citation
“…SVG is a vector sum of spatial QRS and T vectors, reflecting implication of the spatial QRS‐T angle 9. Spatial QRS‐T angle is a well‐known marker9 of the risk of ventricular tachyarrhythmias10 and sudden cardiac death (SCD)11, 12 in the general population, heart failure (HF) patients, and other populations 13, 14…”
Section: Introductionmentioning
confidence: 99%